META ANALYSIS OF THE EFFECT USING STUDENT WORKSHEET ON KNOWLEDGE ASPECTS IN PHYSICS LEARNING - Andala Dika Putri; - Murtiani; - Desnita; Wahyuni Satria Dewi (Universitas Negeri Padang, 2021)
Physics learning process is generally teacher-centered and does not provide opportunities for students to develop their potential by issuing their ideas. The learning is not by the demands of the 2013 curriculum, which is student-centered, students who find a concept in learning. Many studies use student worksheets that measure aspects of student knowledge. Therefore, this study aims to determine the effect size of worksheets on aspects of student knowledge. This research uses the meta-analyst method. Data collection was done by browsing e-journals, SINTA and Google scholar. The data used are several articles published from 2013-2021 through national and international accredited journals. The sample of this study was 55 articles, consisting of 45 national articles and 10 international articles. The articles used have met the criteria for calculating effect size. Three indicators compare the effect of using LKS based on student knowledge grade level, subject matter units, and learning models. Based on the study results, it was found that the effect size of the use of LKS on the three indicators was (1) The largest effect size is obtained on class level indicator, with high category in class XI of 0.73 with medium category. (2) on unit subject indicator, largest effect size is on the fluid material unit of 0.77 with a high category. And (3) on indicator of the learning model, the largest effect size on the project based learning model is 0.86 with a high category.